Nanobarcoding: Topological Transformation‐Based Nanobarcoding for Detection and Enumeration of MicroRNAs and Single Nucleotide Polymorphism (Adv. Biosys. 7/2019). Issue 7 (12th July 2019) - Yuk, Ji Soo; Shin, Seung Won; Chun, Sang Hun; Ku, Bo Mi; Choi, Yu Jeong; Lim, Yong Taik; Luo, Dan; Ahn, Myung‐Ju; Um, Soong Ho
Abstract : In article number1900013, Soong Ho Um and co‐workers report a new topological transformation‐based nanobarcoding technique for the detection and enumeration of short RNAs like microRNAs and their single nucleotide polymorphisms. The RNA from tissue or plasma specifically binds to the side edge of the DNA triangle prism structures on graphene oxide layers, instantly leading to induced fluorescence barcoded emissions.